2011
DOI: 10.3109/13693786.2011.565485
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between TLR2, TLR4, and mannose receptors with gp43 fromParacoccidioides brasiliensisinduce cytokine production by human monocytes

Abstract: The glycoprotein gp43 is an immunodominant antigen secreted by Paracoccidioides brasiliensis, the agent of paracoccidioidomycosis. The present study evaluated whether gp43 can interact with toll-like (TLR2, TLR4) and mannose (MR) receptors on the surface of human monocytes, and how that affects their expression and cytokine production. Monocytes were incubated with or without monoclonal antibodies anti-TLR2, anti-TLR4, or anti-MR, individually or in combination, prior to the addition of gp43. The gp43 binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
2
27
0
3
Order By: Relevance
“…CR3 and MR recognize P. brasiliensis conidia [30], while gp43, the immunodominant antigen of P. brasiliensis , was shown to bind to the MRs and inhibit the phagocytic and fungicidal ability of peritoneal macrophages from susceptible and resistant mice [31]. Two recent studies with human monocytes have also suggested that MR, TLR2, TLR4, and dectin-1 contribute to the recognition of gp43 and P. brasiliensis yeasts, indicating important roles for these pathogen receptors in the immune response against the fungus [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…CR3 and MR recognize P. brasiliensis conidia [30], while gp43, the immunodominant antigen of P. brasiliensis , was shown to bind to the MRs and inhibit the phagocytic and fungicidal ability of peritoneal macrophages from susceptible and resistant mice [31]. Two recent studies with human monocytes have also suggested that MR, TLR2, TLR4, and dectin-1 contribute to the recognition of gp43 and P. brasiliensis yeasts, indicating important roles for these pathogen receptors in the immune response against the fungus [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are found in virtually all tissues and are among the first cells to encounter an invading microorganism. The recognition capacity of the MR is broad allowing for the capture and uptake of a variety of pathogens including Paracoccidioides brasiliensis [26,27] Candida albicans [28], Leishmania donovani [29], Mycobacterium tuberculosis [30,31], Pneumocystis jirovecii ( formally Pneumocystis carinii sp . hominis ) [32], Klebsiella pneumoniae [33], HIV [11,34], Dengue [35], Hepatitis B [36], and influenza A [10,37].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that P. brasiliensis could be phagocytosed by the use of mannose and dectin-1 receptors, 100 as proposed in previous studies. [101][102][103] By studying the predominant DC and associated cytokine types, Pina et al explored other mechanisms that could explain the resistance and susceptibility of mice to infection. In their study, Pina et al found that when infected with P. brasiliensis, there was a predominance of myeloid bone marrow DCs in susceptible (B10.A) mice and plasmacytoid DCs in resistant (A/J) mice.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%